Iron-reducing - and -proteobacteria isolated from laboratory-scaled heterotrophic feammox bioreactor - Chung, Le Phuong; Hai, Nguyen Thi; Quyen, Nguyen Huynh Minh; Hai, Pham The; Hang, Dinh Thuy (Vietnam Journal of Biotechnology, 2021)
Ammonium removal from wastewater is a crucial step in wastewater treatment. Presently employed technologies based on nitrification/denitrification and partial nitritation/anammox principles require oxygen for the nitrification step, and are therefore still not yet fully satisfied with the application practice. In recent years, biological ammonium oxidation coupled with ferric iron reduction (feammox) has been proposed to be responsible for the nitrogen loss in different ecological habitats. Related to the wastewater aspect, the feammox principle has been discussed as an alternative approach for ammonium removal without dependency on oxygen. From a laboratory-scaled feammox bioreactor operated under neutral pH, two bacterial strains FN7 and FN9 were isolated by using the anaerobic Hungate technique. Comparative analyses of 16S rDNA sequences showed that these strains were most closely related to the b-proteobacterium Aciclyphilus denitrificans and the g-proteobacterium Pseudomonas stutzeri, respectively. Although being phylogenetically apart, strains FN7 and FN9 shared several common physiological characteristics that are considered meaningful for the feammox process, i.e. (i) heteroptrophic ammonium oxidation, (ii) denitrification, and (iii) ferric iron reduction. These isolates are proposed to play certain roles in the studied feammox system, contributing to the ammonium removal under heterotrophic feammox condition. The 16S rDNA sequences of strains FN7 and FN9 were available in GenBank under the accession numbers LC474369 and MT568614, respectively.